2020
DOI: 10.3897/compcytogen.v14i2.51154
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular cytogenetic characterization of five wild Vigna species (Fabaceae)

Abstract: To extend our knowledge on karyotype variation of the genus Vigna Savi, 1824, the chromosomal organization of rRNA genes and fluorochrome banding patterns of five wild Vigna species were studied. Sequential combined PI (propidium iodide) and DAPI (4',6-diamidino-2-phenylindole) (CPD) staining and fluorescence in situ hybridization (FISH) with 5S and 45S rDNA probes were used to analyze the karyotypes of V. luteola (Jacquin, 1771) Bentham, 1959, V. vexillata (Linnaeus, 1753) A. Richard, 1845, V. minima (Roxburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(196 reference statements)
1
6
0
Order By: Relevance
“…Nonetheless, occurrence of centromeric CMA + or DAPI + bands along with nucleolar CMA + /DAPI + or CMA 0 bands certainly advocate atypical heterochromatin composition in Lens. The non-uniform composition and rearrangements of heterochromatin had been observed repeatedly in Pailionoideae species (Moscone et al 1999;Souza and Benko-Iseppon 2004;Pedrosa-Harand et al 2006;Mondin and Aguiar-Perecin 2011;She et al 2020), which becomes apparent in our study once again.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Nonetheless, occurrence of centromeric CMA + or DAPI + bands along with nucleolar CMA + /DAPI + or CMA 0 bands certainly advocate atypical heterochromatin composition in Lens. The non-uniform composition and rearrangements of heterochromatin had been observed repeatedly in Pailionoideae species (Moscone et al 1999;Souza and Benko-Iseppon 2004;Pedrosa-Harand et al 2006;Mondin and Aguiar-Perecin 2011;She et al 2020), which becomes apparent in our study once again.…”
Section: Discussionsupporting
confidence: 84%
“…However, we found that the intensity of the nucleolar CMA signals (type A) varies in certain cultivars, suggesting differences in NORs that influence affinity towards the stain. Intraspecific rDNA variation has been thoroughly worked out in Phaseolus (Moscone et al 1999;Pedrosa-Harand et al 2006) and Vigna (Bortoleti et al 2012;She et al , 2020 of Papilionoideae. A number of factors such as transposition, unequal crossing over, inversion or locus duplication, had been suggested to drive NOR variation in plant groups, including Papilionoideae (Moscone et al 1999;Chung et al 2008;Raskina et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such discrepancies in karyotype formula were probably due to differences in analyzed materials and mitotic stages used, and difficulty in identifying chromosomes using the classical staining technique before (She et al 2015a(She et al , 2015b(She et al , 2017(She et al , 2020. This observed difference could mainly be related to variation in the chromosome condensation levels of measured cells (She et al 2015a(She et al , 2020.…”
Section: Karyotype Analysismentioning
confidence: 99%
“…Such discrepancies in karyotype formula were probably due to differences in analyzed materials and mitotic stages used, and difficulty in identifying chromosomes using the classical staining technique before (She et al 2015a(She et al , 2015b(She et al , 2017(She et al , 2020. This observed difference could mainly be related to variation in the chromosome condensation levels of measured cells (She et al 2015a(She et al , 2020. Therefore, differences in the chromosome structures due to the variation in morphology of Allium species, such as variation in cloves of both variations garlic, in size and color of both variation onion (Table 1) and because of the effects of environmental factors such as water, air, soil and maybe nutrients (Saensouk and Saensouk 2021a, b).…”
Section: Karyotype Analysismentioning
confidence: 99%